Tips In Implementing Discipline In The Foundation Children (Case Study At Aisyiyah Orphanage Koto Tangah Branch, Padang City) - Rila Edlin; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by the many neglected children in Indonesia, especially in West Sumatra. This causes many foster children who lack discipline in their daily lives at the Aisyiyah Orphanage, Koto Tangah Branch, Padang City. This study aims to find out the tips for instilling discipline in foster children, especially describing the form of discipline instilled in foster children, tips in instilling discipline through habituation in foster children, and knowing the supporting factors and inhibiting factors in instilling discipline in foster children. .This type of research uses a qualitative approach using the case study method. The sources of data in this study who became the research subjects were the caregivers at the Aisyiyah orphanage, while the informants were those who provided information about the research being carried out, namely the head of the orphanage, representatives of the orphanage and foster children of the Aisyiyah orphanage, Koto Tangah Branch, Padang City. In this study, researchers used observation techniques, interview techniques and documentation techniques.The results showed that (1) the forms of discipline instilled by caregivers in foster children include time discipline and worship discipline, (2) tips for caregivers in instilling discipline through habituation in foster children include teaching children to be routine in activities and teaching children to be consistent. in acting, (3) supporting factors including between caregivers and administrators must be in line, caregivers and administrators provide approaches in the form of mutual love and affection for each other. While the inhibiting factors include facilities and infrastructure, the influence of relationships in the environment, the influence of family behavior at home.Keywords: Caregivers, discipline